What is the relationship between ecosystem services and farmers’ livelihoods? Based on measuring the contribution of ecosystem services to farmers’ livelihoods - Zhou, Lilei; Guan, Dongjie; Sun, Lingli; He, Xiujuan; Chen, Maolin; Zhang, Yongchuan; Zhou, Lianjie (Frontiers in Ecology and Evolution, 2023)
The relationships between ecosystem services and farmers’ livelihoods are important for ecological and livelihood sustainability. In this paper, Chongqing was picked up as a case to elucidate the contribution of ecosystem services to farmers' livelihoods. First, we constructed a DPSIR (driver, pressure, state, impact and response) framework of ecosystem services and farmers’ livelihoods through participatory farmers’ livelihoods surveys and empirical data from the literature. Then, a 48-node Bayesian network model were used to explore the explicit and implicit impacts of both ecosystem services and farmers’ livelihoods, and to determine the key factors. Finally, we analyzed the contribution of ecosystem services to different types of farmers’ livelihoods. The results showed that ecosystem services have a significant impact on the farmers’ livelihoods. The probabilities of high state for ecosystem services and livelihood outcomes were 17.6% and 30.7%, respectively. while the probabilities of medium state were 51.2% and 45.4%, respectively. Particularly for low-income farmers, the impact on them increased with the increasing of ecosystem services (such as aesthetic landscapes and food production). For different types of farming households, the most important contributor of ecosystem services-related income were pure farming households, part-time farming households and nonfarming households, accounting for 77.3%, 36.3% and 14.8% of the total average annual household income, respectively. Our findings suggested that in promoting sustainable management of ecosystems, the contribution of ecosystem services to farmers' livelihoods and their impact on farm income and the ecosystem services value should be considered.